Attitude to RSV Vaccination Among a Cohort of Pregnant Women in Jordan: A Cross‐Sectional Survey Study - Malik Sallam; Tleen Kherfan; Amwaj Al‐Farajat; Leen Nemrawi; Nada Atawneh; Rand Fram; Ala'a B. Al‐Tammemi; Muna Barakat; Kamil Fram (Health Science Reports)
ABSTRACT Background and Aims The recently approved maternal vaccination against respiratory syncytial virus (RSV) can reduce its burden among infants. However, vaccine hesitancy/resistance can undermine the beneficial impact of RSV vaccination. The aim of this study was to assess the willingness of pregnant women in Jordan to receive RSV vaccination and its associated determinants. Methods Face‐to‐face interviews were conducted in obstetrics/gynecology clinics in the Central, Northern, and Southern regions of Jordan during January–February 2024, using a convenience sampling approach. Attitude to RSV vaccination was assessed using the previously validated ABCDEF scale. Results A total of 404 pregnant women participated in the study with a mean age of 30.1 ± 6.2 years. A majority of the participants showed willingness to receive RSV vaccination (n = 313, 77.5%), with hesitancy among 25 participants (6.2%), and resistance among 66 participants (16.3%). Variables that were significantly associated with a higher RSV vaccine acceptance in multivariate analysis were: age < 30 years (adjusted odds ratio (aOR): 2.45, p = 0.010), undergraduates (aOR: 3.27, p = 0.026), being a healthcare worker (aOR: 4.50, p = 0.036), and the history of previous COVID‐19/influenza vaccine uptake (aOR: 2.47, p = 0.045). Two out of the six ABCDEF constructs were significantly associated with RSV vaccine acceptance, namely the “Advice” construct (aOR: 10.38, p < 0.001) and the “Fear” construct (aOR: 21.49, p < 0.001). Conclusion This study highlighted the complex nature of attitude towards maternal RSV vaccination among pregnant women. The study showed the role of demographic variables, prior vaccination experience, trust in credible health institutions and vaccine safety, and the fear of RSV disease consequences in infants in shaping maternal attitude to RSV vaccination. Addressing these factors can help to effectively promote RSV vaccine uptake among pregnant women, subsequently helping to protect infants from the significant RSV disease burden.